1998
DOI: 10.1111/j.1346-8138.1998.tb02401.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical PUVA Therapy for Chronic Hand Eczema

Abstract: Seventeen patients with persistent chronic hand eczema were treated with topical 0.1% 8-methoxypsoralen and UVA (PUVA) for 8 weeks. Significant improvement was achieved in 5 cases (29%), moderate improvement in 9 (53%), and little improvement in 3 (18%). The mean number of PUVA treatments was 22.2, and the mean total UVA dose was 63.5 J/cm2. There was no association between clinical response and duration of hand eczema, positive patch test reaction, or atopic status. Since topical PUVA has no risk of systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
0
18
2
2
Order By: Relevance
“…The 51.3% positive response to topical PUVA identified by this study is disappointing in comparison with results quoted elsewhere (6–10). One possible explanation for this is a lower mean number of treatments (18.4) compared with other studies [22.2 and above (6–9)]. Indeed using multivariate analysis, we found the number of treatments to be a statistically significant variable ( P =0.04).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The 51.3% positive response to topical PUVA identified by this study is disappointing in comparison with results quoted elsewhere (6–10). One possible explanation for this is a lower mean number of treatments (18.4) compared with other studies [22.2 and above (6–9)]. Indeed using multivariate analysis, we found the number of treatments to be a statistically significant variable ( P =0.04).…”
Section: Resultscontrasting
confidence: 99%
“…Interestingly, the study by Taylor et al (8) found that an a mean 41 treatments were required to induce clearing, whereas none of our study group received more than 35. The average cumulative UVA dose was also lower than that found in other studies (6–10). This is not surprising as the number of treatments is a major contributor to the cumulative dose.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Psoralen plus ultraviolet therapy may be considered as a second-line option when topical corticosteroids are ineffective. Although its efficacy is limited, it is considered to be relatively safe (3,7). Systemic treatments are indicated for refractory CHE, the majority of which have not been investigated in randomized clinical trials and are therefore prescribed off-label (2,3,8).…”
Section: Introductionmentioning
confidence: 99%
“…Over 80% of patients had at least a moderate improvement in symptoms. The results were independent of duration of hand eczema, positive patch test reaction or atopic status [79]. Topical corticosteroids have also been effective in the treatment of hand eczema.…”
Section: Infantile Eczemamentioning
confidence: 97%